2019
DOI: 10.35787/jimdc.v8i4.282
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Stress among Parents of Hearing Impaired versus Intellectually Disabled Pakistani Children

Abstract: Background: Parents of special children face physical, psychological and social impact of their child’s disability, including hopelessness and depression. This study is important as it will help professionals plan and provide effective coping strategies so parents could have a positive perception and behavior for disabilities (like hearing impaired and intellectual disability) in their children. The objective of this study was to analyze level of psychological stress among parents of children with hearing impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…20 Similarly in a local study moderate level of stress was reported in parents of HI compared to intellectually challenged where profound stress was reported. 21 Ebrahimi H et al reported that parents of HI live with fear of having another HI baby in the next pregnancy. 22 In the present study the number of special children seem to be related to increase in parental stress with minimum stress with one special child.…”
Section: Discussionmentioning
confidence: 99%
“…20 Similarly in a local study moderate level of stress was reported in parents of HI compared to intellectually challenged where profound stress was reported. 21 Ebrahimi H et al reported that parents of HI live with fear of having another HI baby in the next pregnancy. 22 In the present study the number of special children seem to be related to increase in parental stress with minimum stress with one special child.…”
Section: Discussionmentioning
confidence: 99%
“…The findings are supported by Padden et al [20], Sabih and Sajid [21], and Ishtaiq et al [2], reporting a signifi-cant level of stress in parents of ASD children. Firdouset al [22] also recounted more stress in parents of children with intellectual disabilities than mothers of hearingimpaired children. Regarding mothers' characteristics, most mothers belonged to the middle class, 30-40 years old, well educated, but non-working.…”
Section: Discussionmentioning
confidence: 99%